A Review: Application of Bioremediation and Phytoremediation Techniques for Heavy Metal Contamination in Mining Areas of Sulawesi, Indonesia - Fitria Azis; Nurfadini Nurfadini; Ahyar Ahmad; Amalyah Febryanti; Sappewali Sappewali; Dian Fitrah Ardita R; Nur Asmi; Harningsih Karim (Jurnal Ilmu Lingkungan, 2025)
Mining has been a practice spanning millennia, leaving behind a legacy of mine waste containing hazardous substances, including various metals in nearly every country. Indonesia is one of the most nickel-rich regions in the world. Some of these resources are located in the Sulawesi and North Maluku regions. Sulawesi includes Central Sulawesi, South Sulawesi and Southeast Sulawesi. Pollutants in the form of mercury metal (Hg), lead metal (Pb), cadmium metal (Cd), and chromium metal (Cr) are considered toxic and difficult to remove due to their stable nature. Effective remediation methods are imperative in response to this issue, among which bioremediation and phytoremediation stand out. Bioremediation employs microorganisms to detoxify the environment of heavy metals, while phytoremediation utilizes plants for the same purpose. Both methods involve intricate interactions among plants, microbes, and their substrates to purify the environment and facilitate further filtration. Bioremediation encompasses two primary approaches: the in-situ method and the ex-situ method. In situ methods include bioventing, biosparging, bioaugmentation, and biostimulation. Ex-situ methods, contaminated soil or water is retrieved from its origin and purified elsewhere by living organisms; this process utilizes bioreactors, aeration, steam regulation, and additional nutrients to increase the rate of pollutant decomposition. The bioremediation mechanism involving microorganisms employs biosorption, bioaccumulation, biotransformation, and bioleaching. Phytoremediation employs several methods, including phytoextraction, phytofiltration, phytovolatilization, phytodegradation, and phytodesalination. Identifying efficient hyperaccumulators is the most direct approach for successful heavy metal phytoremediation. Bioremediation and phytoremediation techniques are economical and suitable solutions to address heavy metal pollution in polluted environments. With a deeper understanding of these techniques, it is hoped that we can more effectively address these complex environmental challenges, particularly in mining areas in Sulawesi, Indonesia.